Benchmarking the Financial Performance, Growth, and Outreach of Greenfield Microfinance institutions in Sub-Saharan Africa - Cull, Robert; Harten, Sven; Nishida, Ippei; Bull, Greta (World Bank Group, Washington, DC, 2014)
In recent years there has been a rapid increase in the presence and growth of greenfield microfinance institutions in Sub-Saharan Africa. This paper uses regressions to benchmark those African greenfields relative to other microfinance providers and finds that greenfields grew faster in terms of deposits and lending, improved their profitability to levels comparable to the top microfinance institutions, and substantially increased their lending to women. The effects were especially strong for greenfields that followed a consultant-led model to establish a deep retail banking presence spanning multiple countries, including the creation of extensive branch networks. Although their loan sizes are somewhat larger than those of most African microfinance institutions, indicating less outreach to the poorest market segments, greenfields have achieved rapid gains in financial inclusion on a broad scale.